Evaluation of the cyanide pollution in artisanal mining in La Bola de Igor hill by using GIS and Kriging regression (SCIÉNDO INGENIUM, 2021)
This study is based on the evaluation of the environmental impact generated by artisanal gold mining, the origin of environmental pollution being the leaching process with cyanide, through which the water from the watersheds is polluted, agricultural soil is degraded, and cyanide compounds are released. The study area corresponds to the La Bola de Igor hill, Huaranchal, where soil samples were collected to determine the cyanide concentration. Through the use of a Geographic Information System, it was possible to georeference the sampling points and the application of the Kriging regression method to study the propagation dynamics of free cyanide and identify the most affected areas in need of intervention for the restoration of degraded ecosystems. The results indicate that the area with the most significant risk of contamination by cyanide corresponds to the river's vicinity downstream from the source of contamination, exceeding the limits established in Peruvian regulations. Finally, the cyanide contamination maps obtained in this research support decision-making regarding the remediation of environmental pollution in the study area.
Keywords: cyanide; mining pollution; gold; Geographical Information Systems; Kriging regression